Estudio de Prefactibilidad para la Constitución de una Empresa Retail dedicada a la Comercialización de Productos Chinos en la ciudad de Trujillo - Cabrera Vilca, Carlos Eduardo (2019)
The idea of setting up a retail company is distributed to the conversion of Chinese products in the city of Trujillo arises due to the new trends that are available, as well as providing a product with more features, for all that is said the present study is carried out. The project starts with a complete methodology for the analysis and implementation of the company and will address issues ranging from the analysis of the environment and its influence on the company, requirements and process for the constitution of the company that allows determining the sustainable competitive advantages in time, market research with secondary sources, an analysis of current potential market data is carried out through the data of the Association of Exporters (ADEX), in order to determine the potential demand and what will be the target market that is planned to meet. In the technical study, the macro and microlocalization of the company is analyzed. It was determined where the location of the company will be located. In addition, the optimal distribution of the company's environments and the size in m2 was made. Finally, the Financial Plan states that the sources of financing will be made up of contributions from shareholders with 70% and 30% of debt with a local bank, the initial investment for the project amounts to S / 181.747,93. Calculated the financial statements and cash flow, based on the budgets required for this purpose, you get a VANE of S / 257.516,12 and a VANF of 261.232,76, you also get a TIRE of 58,37% and an ITRF of 68,77%, the project will also have a recovery period of 2 years, 2 months and 11 days. For all this, it can be concluded that the constitution of a retail company selling Chinese products in the city of Trujillo for the year 2019, is viable in terms of market, technical, economic and financial, according to the preparation of this study.